2013
DOI: 10.1371/journal.pone.0058738
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Liver Support System Combined with Liver Transplantation in the Treatment of Patients with Acute-on-Chronic Liver Failure

Abstract: BackgroundThe search for a strategy to provide temporary liver support and salvage the patients with acute-on-chronic liver failure (ACLF) remains an important issue. This study was designed to evaluate the experience in artificial liver support system (ALSS) combined with liver transplantation (LT) in the treatment of ACLF.Methodology/Principal FindingsOne hundred and seventy one patients with HBV related ACLF undergoing LT between January 2001 and December 2009 were included. Of the 171 patients, 115 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…However, contrary results were shown by systematic review by Kjaergard et al where it was seen that ALS reduced mortality by 33 % in patients with ACLF as compared to SMT [131]. More recently, studies have shown that ALS could be an effective form of bridging therapy in patients with ACLF with high MELD scores awaiting liver transplantation and many believe it is a futile exercise in the absence of liver transplant [119,120]. These results have been substantiated by the recently published two large European randomized multicentric controlled trials, i.e., HELIOS (for Prometheus) [125] and RELIEF trial (for MARS) [124], that failed to show any benefit with these modalities on short-term transplant-free survival, which was the primary end point of these studies.…”
Section: Liver Transplantationmentioning
confidence: 96%
See 1 more Smart Citation
“…However, contrary results were shown by systematic review by Kjaergard et al where it was seen that ALS reduced mortality by 33 % in patients with ACLF as compared to SMT [131]. More recently, studies have shown that ALS could be an effective form of bridging therapy in patients with ACLF with high MELD scores awaiting liver transplantation and many believe it is a futile exercise in the absence of liver transplant [119,120]. These results have been substantiated by the recently published two large European randomized multicentric controlled trials, i.e., HELIOS (for Prometheus) [125] and RELIEF trial (for MARS) [124], that failed to show any benefit with these modalities on short-term transplant-free survival, which was the primary end point of these studies.…”
Section: Liver Transplantationmentioning
confidence: 96%
“…Whether these could be considered for transplant and what is the outcome when compared with those without organ failure is not clear. Ling et al and Xu et al found that downgrading MELD (to \ 30) in ACLF using an artificial liver support system as bridging therapy improved outcomes in the responders to levels similar to those who had upfront liver transplant [119,120].…”
Section: Liver Transplantationmentioning
confidence: 99%
“…From the 1 Departments of Research and 3 Hepatology, Institute of Liver & Biliary Sciences (ILBS), New Delhi, India; 2 Institute of Bioinformatics, International Technology Park, Bangalore, India; Departments of 4 Biological Chemistry, 5 Pathology, and 6 Oncology, McKusick-Nathans Institute of Genetic Medicine, Johns Hopkins University School of Medicine, Baltimore, MD; and 7 Department of Pathology, ILBS, New Delhi, India.…”
mentioning
confidence: 99%
“…5 Dysregulated iron homeostasis has been reported in patients with CLD, particularly with alcohol-related liver disease, wherein iron overload is directly correlated with alcohol consumption 6 and labile iron pool (LIP), which promotes formation of oxygen radicals and increases oxidative stress in hepatocytes. 7,8 Increased iron levels in the liver and macrophages also contribute to liver damage and apoptosis.…”
mentioning
confidence: 99%
“…For patients who developed massive necrosis of hepatocytes and lost ability of liver regeneration, several times of ALSS and sequential timely LT were needed [15].…”
Section: Discussionmentioning
confidence: 99%